MicroRNA-574-5p Was Pivotal for TLR9 Signaling Enhanced Tumor Progression via Down-Regulating Checkpoint Suppressor 1 in Human Lung Cancer - Li, Qinchuan; Li, Xiaoman; Guo, Zhongliang; Xu, Feng; Xia, Jingyan; Liu, Zhongmin; Ren, Tao (PLOS ONE, 2012)
Accumulating data suggested that functional expression of Toll-like receptors (TLRs) in tumor cells was involved in tumor progression. Our previous study demonstrated that TLR9 signaling could enhance the tumor progression of human lung cancer cells in vitro and in vivo. We further showed that miR-574-5p was the mostly up-regulated miRNA in human lung cancer cells under TLR9 signaling by miRNA array analysis. Here we characterized the potential role of miRNA-574-5p in enhanced tumor progression induced by TLR9 signaling in human lung cancer. We confirmed that TLR9 signaling effectively elevated the expression of miR-574-5p in human lung cancer cells. Notably, we found that down-regulation of miRNA-574-5p using miR-574-5p inhibitor in vitro or miR-574-5p sponge in vivo significantly abrogated the enhanced tumor progression induced by TLR9 signaling. Further studies showed that miR-574-5p was an important player associated with enhanced tumor progression of human lung cancer cells. Notably, we identified checkpoint suppressor 1 (Ches1) as the dominant direct target for miRNA-574-5p to confer the TLR9 signaling enhanced tumor progression. We revealed that over-expression of Ches1 significantly inhibited the cell cycle entry of human lung cancer cells. Finally, we revealed that the expression of miR-574-5p was positively correlated with TLR9 and reversely correlated with Ches1 in lung cancer patients. Our findings not only facilitated the further understanding of the crosstalk between miRNAs and TLRs in tumor biology, but also provided novel potential candidates for treatment of cancer.